Pharmacokinetic and Pharmacodynamic Considerations in Relation to Calcineurin Usage in Elderly Kidney Transplant Recipients - Cossart, Amelia R.; Isbel, Nicole M.; Scuderi, Carla; Campbell, Scott B.; Staatz, Christine E. (Frontiers in Pharmacology, 2021)
This review summarises how possible age-related changes in tacrolimus and cyclosporine pharmacokinetics and pharmacodynamics may influence drug dosing and monitoring in the elderly, and highlights how micro-sampling may be useful in this cohort in the future. Advancing biological age leads to physiological changes that can affect drug absorption, distribution, metabolism and excretion, as well as immune system responsiveness. Some studies have shown that elderly recipients may have higher dose-adjusted exposure and/or lower clearance of the calcineurin inhibitors, suggesting that doses may need to be lowered in elderly recipients. Only one study has examined how aging effects drug target enzyme activity and demonstrated that age does not correlate with the calcineurin inhibitor half-maximal inhibitory concentration. Several studies have shown elderly kidney transplant recipients have increased risk of both morbidity and mortality, compared to younger adults due to increased susceptibility to immunosuppressant side effects, particularly cardiovascular disease, infection and malignancy. Current immunosuppressant dosing and monitoring protocols often make no adjustments for age. Lower maintenance immunosuppressant targets in elderly recipients may decrease patient susceptibility to drug side effects, however, further studies are required and appropriate targets need to be established. Blood draw by micro-sampling may be useful for drug monitoring in this cohort in the future, as blood collection is minimally invasive and less painful than venepuncture. Micro-sampling could also make further pharmacokinetic, pharmacodynamics and outcome studies in the elderly more feasible.